2017
DOI: 10.4158/ep171764.gl
|View full text |Cite
|
Sign up to set email alerts
|

American Association Of Clinical Endocrinologists And American College Of Endocrinology Guidelines For Management Of Dyslipidemia And Prevention Of Cardiovascular Disease - Executive Summary

Abstract: A1C = hemoglobin A1C ACE = American College of Endocrinology ACS = acute coronary syndrome AHA = American Heart Association ASCVD = atherosclerotic cardiovascular disease ATP = Adult Treatment Panel apo = apolipoprotein BEL = best evidence level CKD = chronic kidney disease CPG = clinical practice guidelines CVA = cerebrovascular accident EL = evidence level FH = familial hypercholesterolemia HDL-C = high-density lipoprotein cholesterol HeFH = heterozygous familial hypercholesterolemia HIV = human immunodefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(127 citation statements)
references
References 9 publications
2
118
0
7
Order By: Relevance
“…Patients with a history of premature ASCVD were also included in the Extreme Risk group. Treatment goals included an LDL-C <55 mg/dL, with consideration also given to non-HDL-C and Apo B levels [10].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a history of premature ASCVD were also included in the Extreme Risk group. Treatment goals included an LDL-C <55 mg/dL, with consideration also given to non-HDL-C and Apo B levels [10].…”
Section: Introductionmentioning
confidence: 99%
“…
Hypertriglyceridemia is associated with increases in atherosclerotic cardiovascular disease (ASCVD) risk and remains prevalent among adults in the United States (US) due to an increasing prevalence of obesity, insulin resistance, diabetes mellitus, and other risk factors. Guidelines suggest target triglycerides (TG) should be < 150 mg/dL [1]. However, a number of studies have suggested that reduced cardiovascular risk is associated with lower TG [2][3][4].
…”
mentioning
confidence: 99%
“…Aggressive actions to reduce LDL cholesterol are recommended for patients at a higher risk of developing cardiovascular disease (CVD). [3,4] Statins are currently used as first-line therapy for dyslipidemia because they have clear prognostic benefits, such as decreasing CVD incidence and increasing survival rate by lowering LDL cholesterol, with relatively low side effects. [5] Atorvastatin is Atorvastatin and ezetimibe are frequently co-administered to treat patients with dyslipidemia for the purpose of low-density lipoprotein cholesterol control.…”
Section: Introductionmentioning
confidence: 99%